The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18632/aging.103540
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic effects of high uric acid in mice via activation of MEF2C-dependent NF-κB pathway by upregulating let-7c

Abstract: Serum uric acid is reportedly associated with thrombosis development. However, still unclear is the mechanism of high uric acid in thrombosis with the involvement of let-7c. In an aim to fill this void, we conducted this study by treating mice and human umbilical vein endothelial cells with high uric acid. Analysis indicated that let-7c was upregulated in hyperuricemia patients as well as in mice and human umbilical vein endothelial cells treated with high uric acid. Furthermore, high uric acid inhibited myocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…In a recent animal study, increased uric acid levels activated the myocyte enhancer factor-2C-dependent and nuclear factor-κB pathways by let-7c and generating thrombosis. [ 40 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent animal study, increased uric acid levels activated the myocyte enhancer factor-2C-dependent and nuclear factor-κB pathways by let-7c and generating thrombosis. [ 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent animal study, increased uric acid levels activated the myocyte enhancer factor-2C-dependent and nuclear factor-κB pathways by let-7c and generating thrombosis. [40] Despite the large population database, this study had several limitations. First, data from the KoGES did not have all the records regarding potential confounders, including treatment of hyperuricemia, duration of disease, drug intake, and coronary angiography procedure; as such, the results should be interpreted with caution.…”
Section: Characteristicsmentioning
confidence: 96%
“…Cimmino et al 90 reported that UA at high levels enhanced the procoagulant function of tissue factor (TF) and decreased the expression of its physiological inhibitor TFPI in HUVECs, leading to the acquisition of a prothrombotic phenotype. Similarly, a shorten activated partial thromboplastin time (APTT) and prothrombin time (PT), a prolonged thrombin time (TT), and increased levels of fibrinogen and D‐dimer have been observed in the serum of a HUA mouse model 91 . These effects may have been partially due to myocyte enhancer factor 2C (MEF2C)‐dependent nuclear factor kappa B (NF‐κB) activation in ECs, which is regulated by let‐7c and results in significant increases in the protein levels of plasminogen activator inhibitor 1 (PAI‐1) and TF but marked reductions in tissue plasminogen activator (t‐PA) expression 91 .…”
Section: Mechanisms Underlying Hua‐induced Edmentioning
confidence: 96%
“…Similarly, a shorten activated partial thromboplastin time (APTT) and prothrombin time (PT), a prolonged thrombin time (TT), and increased levels of fibrinogen and D-dimer have been observed in the serum of a HUA mouse model. 91 These effects may have been partially due to myocyte enhancer factor 2C (MEF2C)-dependent nuclear factor kappa B (NF-κB) activation in ECs, which is regulated by let-7c and results in significant increases in the protein levels of plasminogen activator inhibitor 1 (PAI-1) and TF but marked reductions in tissue plasminogen activator (t-PA) expression. 91 In addition, endothelial microparticles (MPs) participate in the mechanism underlying HUA-induced coagulation.…”
Section: Procoagulant Activitymentioning
confidence: 99%
“…Moreover, let 7-c is interconnected with platelets functionality. In a study performed on an animal model of hyperuricemia, increased levels of SUA generated thrombosis through the activation of MEF2C-dependent and NF-ƙB pathways by let 7-c [ 23 ]. In mice, the inhibition of xanthine oxidase by febuxostat led to a decrease in the expression of PAI-1 and TF, thus diminishing the prothrombotic state [ 24 ].…”
Section: Mechanistic Frameworkmentioning
confidence: 99%